New records and updates on alien Auchenorrhyncha species in Serbia - Šćiban, Marko; Kosovac, Andrea (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
During a 2019 survey of the Auchenorrhyncha fauna in Serbia, three alien specieswere recorded for the first time: a leafhopper species of Asian origin Orientus ishidae(Cicadellidae, Deltocephalinae) and two North American species, Acanalonia conica(Acanaloniidae) and Erasmoneura vulnerata (Cicadellidae, Typhlocybinae). Besidesthese first findings, the presence of the leafhopper Phlogotettix cyclops (Cicadellidae,Deltocephalinae) was confirmed in Serbia after its initial record more than a century ago.Other allochthonous species already known to be present in local entomofauna werealso found: Japananus hyalinus (Cicadellidae, Deltocephalinae), Scaphoideus titanus(Cicadellidae, Typhlocibynae), Stictocephala bisonia (Membracidae) and Metcalfa pruinosa(Flatidae). The newly detected Auchenorrhyncha species in Serbia, O. ishidae, A. conica andE. vulnerata, as well as Ph. cyclops, are recognized as either tentative or true grapevine pestsin Europe that cause physical damage or induce phytoplasma-borne diseases. Our findingsreveal a potential phytosanitary risk that can emerge in Serbian vineyards in upcomingyears and support refocused research of Auchenorrhyncha diversity in natural habitats,rather than in agroecosystems and their immediate surroundings.
Keywords: Auchenorrhyncha, diversity, alien species, Serbia